Acceptability and preferences for long-acting antiretroviral formulations among people with HIV infection. Issue 6 (3rd June 2021) - Dandachi, Dima; Dang, Bich N.; Lucari, Brandon; Swindells, Susan; Giordano, Thomas P.
ABSTRACT: The study evaluates the acceptability and preferences for long-acting antiretroviral therapy (LA-ART) among a diverse cohort of people with HIV infection (PWH). It consists of a self-administered survey and chart review of PWH presenting to an HIV clinic in Houston, Texas, between February and June 2018; 374 participants were included; 61% indicated that they were likely or very likely to use LA-ART formulations. When asked about preference, 41% preferred pills, 40% preferred injections, and 18% preferred an implant. The most common benefit reported was eliminating the need to remember taking daily HIV pills (74%); 43% were worried that LA-ART will not be as effective as pills. Participants with a college degree, men who have sex with men, and ART-experienced were more willing to use LA-ART. Participants who reported poor or fair health, or who screened positive for depression or anxiety were significantly less willing to use LA-ART. The likelihood of using LA-ART did not correlate with self-reported adherence and HIV suppression. Patients with difficulty scheduling and attending clinic visits preferred injections and implant over pills. Most participants indicated a willingness to use new LA ART formulations. However, 41% still prefers pills, and those more interested in LA-ART were not less adherent.